Two Decades of Business Competition Law: How has Indonesian Competition Law Transformed? - Baiquni, Muhammad Iqbal; Waspiah, Waspiah (Faculty of Law, Universitas Negeri Semarang, 2023)
This research focuses on the development of competition law in Indonesia, specifically examining the role and impact of Law No. 5 of 1999 concerning the Prohibition of Monopolistic Practices and Unfair Business Competition, also known as the Business Competition Law. The objective of this research is to provide an overview of the various changes in business competition law in Indonesia, particularly the establishment of the Business Competition Supervisory Commission (KPPU), responsible for enforcing the law against business competition violations committed by companies or individuals. Additionally, this article will compare Indonesian competition law with that of other countries, such as Australia and Singapore. The research adopts two main methods: a statute approach and a comparative approach. The statute approach involves analyzing three statutory regulations: Law No. 5 of 1999 (Indonesia), Australia Competition and Consumer Amendment Act 2013 (Australia), and Singapore Competition Act 2004 (Singapore). The findings of this study reveal two key weaknesses in Indonesia's Business Competition Law. First, there are deficiencies in both the material and formal aspects of determining prohibitions per se or employing the rule of reason theory. Secondly, there are concerns related to the definition of dominant market positions, necessitating a review of the Business Competition Law to align it with best practices. Additionally, there are issues regarding the neutrality of KPPU as a Quasi-Judicial institution, and the need to safeguard the rights of the reported parties during the judicial process at KPPU. Furthermore, a legal comparison with Australia and Singapore highlights that Indonesia's Business Competition Law lags behind in several areas, resulting in a legal vacuum concerning Mergers and Acquisitions Regulations, Horizontal and Vertical Agreements, Dispute Resolution, and Consumer Protection. In conclusion, this research emphasizes the significance of robust competition laws in promoting fair business competition, economic growth, and foreign investment. It sheds light on the weaknesses of Indonesia's current Business Competition Law and suggests potential areas for improvement based on a comparison with competition laws in Australia and Singapore. Addressing these issues would strengthen Indonesia's competitive landscape and foster a more conducive business environment.